Determination of tip profile for atomic force microscopy - Tale, Camtu (2010)
In this study, atomic force microscopy (AFM) tip profile was introduced and examined on carbon nanotubes with varied diameters. Indeed, this technique is a promising candidate for imaging the objects at nano-scale under 10 nm due to the sharply apex of AFM’s tips . In addition, it could apply for biology samples such as DNA, proteins, cells, etc, which have larger sizes and more sensitive surfaces. Therefore, AFM tip shapes have been emerged and studied throughout. Subsequently, the image information has been analyzed in order to estimate the AFM tip profile. The image analysis has been characterized by many programs especially Surface program and Matlab. The purpose of our work is to present different approaches of examination AFM tips on 2 nm - 10 nm carbon nanotubes’ diameters.